Repeated carbon nanotube administrations in male mice cause reversible testis damage without affecting fertility - Bai, Yuhong (2010)
Soluble carbon nanotubes are promising materials for in vivo delivery and imaging applications. Several reports have described the in vivo toxicity of carbon nanotubes, however, their effects on male reproduction have not been examined. Here we show that repeated intravenous injections of water-soluble multi-walled carbon nanotubes into male mice can cause reversible testis damage without affecting fertility. Nanotubes accumulated in the testes, generated oxidative stress, and decreased the thickness of the seminiferous epithelium in the testis at day 15, but the damage was repaired after 60 and 90 days. The quantity, quality, and integrity of the sperm and the levels of three major sex hormones were not significantly affected throughout the 90-day period. The fertility of treated male mice was unaffected; the pregnancy rate and delivery success of female mice that mated with the treated male mice did not differ from those that mated with untreated male mice.